Reliability and validity of the Japanese version of the selective control assessment of the lower extremity tool among patients with spastic cerebral palsy - Kusumoto, Yasuaki (J Phys Ther Sci, 2016)
[Purpose] The aim of this study was to translate the Selective Control Assessment of the Lower Extremity (SCALE) tool from English to Japanese and to assess the reliability and validity of the Japanese version of the SCALE (SCALE-J) tool in Japanese patients with spastic cerebral palsy. [Subjects and Methods] The SCALE tool was translated into Japanese in accordance with the published guidelines. In total, 55 patients with spastic cerebral palsy were enrolled in the present study. Reliability by internal consistency (Cronbach’s α), intrarater reliability, inter-rater reliability, and convergent validity by comparing Gross Motor Function Classification System (GMFCS) scores were examined. [Results] The Cronbach’s α value of the SCALE-J tool was 0.97–0.98, whereas that of the intrarater and inter-rater reliability ranged from 0.93 to 0.96. The Spearman correlation coefficient revealed a good relationship between the SCALE tool and the GMFCS. [Conclusion] The SCALE-J tool was found to be reliable and valid; therefore, the SCALE tool may be useful for evaluation in clinical practice.